Fatores de risco comportamentais e metabólicos associados a depressão, risco de suicídio e fenótipo de risco vascular em adolescentes: Coorte RPS, São Luís - BARBOSA, Janaina Maiana Abreu (2021)
Adolescence is a sensitive period of human development, and greater exposure to risk behaviors for Non-Communicable Diseases (NCD), such as smoking, physical inactivity, unhealthy diet and harmful use of alcohol, can have repercussions on mental health, insulin sensitivity, diabetes and future cardiovascular risk. This thesis comprises two articles. In the first article, the association of the main risk factors for NCDs with depression and the risk of suicide was evaluated through structural equation modeling considering pathways triggered by social vulnerability or mediated by obesity. This is a population-based study carried out with 2,515 adolescents aged 18 and 19, belonging to the RPS Cohort, from São Luís – MA. Exposures were the main risk factors for NCDs: Substance use behaviors (latent variable deduced from the use of alcohol, tobacco and drugs), physical inactivity and components of the unhealthy diet (added sugar and saturated fat). The body fat index was evaluated by the fat mass index. Outcomes were depression and suicide risk. Substance use behaviors (standardized coefficient SC = 0.304; p <0.001), higher consumption of added sugar (SC = 0.094; p = 0.005) and female gender (SC = 0.310; p <0.001) were associated with depression. Substance use behaviors (SC = 0.356; p <0.001), higher consumption of added sugar (SC = 0.100; p = 0.012) and female gender (SC = 0.207; p <0.001) were also associated with the risk of suicide. Additive NCD risk behaviors have been associated with depression and suicide risk in adolescents, which may explain clustering of NCDs and mental disorders in adulthood. In the second article, the association between the Insulin Resistance Phenotype and Vascular Risk Phenotype was investigated. This is a cross-sectional study with 2,515 adolescents aged 18 and 19, Cohort RPS, from São Luís – MA. A theoretical model was proposed to assess the direct association between the Insulin Resistance Phenotype and Vascular Risk Phenotype at the end of the second decade of life, and indirect pathways starting from social vulnerability, alcohol consumption and body fat in young people. The latent variable Insulin Resistance Phenotype was formed by the HDL Triglycerides ratio (TG/HDL), Triglycerides-Glycemic Index (TyG) and VLDL levels and the Vascular Risk Phenotype was formed by the Systolic Blood Pressure, Diastolic Blood Pressure and Pulse Wave Velocity. Body fat was measured by the fat mass index, measured by dual-emission X-ray densitometry (DEXA). The Insulin Resistance Phenotype was directly associated with the Vascular Risk Phenotype in males (SC=0.183; p < 0.001) and females (SC=0.152; p < 0.001) at the end of the second decade of life. The Insulin Resistance Phenotype mediated the association between the highest body fat index and the Vascular Risk Phenotype in males (SC=0.054; p < 0.001) and females (SC=0.041; p < 0.001). The association between Insulin Resistance Phenotype and Vascular Risk Phenotype in young people is suggestive of common pathophysiological mechanisms in early events on the diabetes and cardiovascular continuums, effect not mediated by body fat.